REINTERPRETING THE HADITH OF ‘AISYAH IN THE CONTEXT OF EARLY MARRIAGE: A MAQĀṢID AL-SHARĪ‘AH AND LEGAL ANALYSIS IN INDONESIA - Waliyuddin Yusuf; Nur Laili Hidayati; Masruhan; Nurlailatul Musyafaah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The phenomenon of early marriage remains a complex social and legal issue in Indonesia, reflecting the gap between religious texts, legal regulations, and societal realities. This research departs from the debate on the hadith of the Prophet Muhammad's marriage to 'Aisha ra. which is often used as a justification for the practice of child marriage. The purpose of this research is to critically analyze the hadith through a socio-historical approach and maqāṣid al-sharī‘ah, and review its conformity with the provisions of Indonesian positive law. The research method used is normative legal research - perspective and qualitative study through literature analysis of the hadiths in Kutub al-Sittah, the views of classical fuqaha, and national legal policies such as Law No. 16 of 2019. The results of the study show that classical scholars permit al-saghirah marriage based on historical context, but contemporary scholars emphasize the need for contextual interpretation for the sake of child protection. The maqāṣid al-sharī‘ah approach emphasizes the importance of principles and maslahah to prevent physical and social harm. From a positive legal perspective, changing the marriageable age limit to 19 represents a harmonization of Islamic law and the principle of children's rights. This study concludes that the hadith of 'Aisyah should be understood as historical fact, not normative legitimacy, and emphasizes the need for adaptive and just Islamic legal ijtihad regarding the protection of children and families